Perancangan Alat Penyemprotan Tanaman Cabai Sistem Kontrol Otomatis Berbasis IoT - Rizkitinus, Fina; Eko Purnomo, Fendik; Adzar Prayoga, Fahrizal; ifnil mubarok, Diki; Ristaulia, Nasikhatul; Reza Rabani, Muhammad (The Indonesian Journal of Computer Science, 2025)
The application of Internet of Things (IoT) technology in the agricultural sector provides innovative solutions in managing chili plant pests. This study aims to design an IoT-based pesticide sprayer with automatic control using Arduino, ESP32, and solar panel energy sources. The Research and Development (R&D) method is used, including problem identification, planning, product development, trials, evaluations, and field validation. The test results show that this tool is capable of spraying water or pesticides up to a distance of 5 meters with a spraying area of 10 m² per cycle. With a spray capacity of up to 12 liters per cycle, this tool has succeeded in reducing the whitefly pest population by 70% and increasing chili plant productivity by 30% compared to manual methods. Energy usage analysis shows the efficiency of the tool through the use of 120 Wp solar panels and 12V 100Ah batteries that support pump operations for 1 hour 48 minutes. This study provides a sustainable solution for managing plant pests and increasing crop yields effectively by utilizing renewable energy.